Superpave and SMA: Mechanistic methods in the engineering of Asphalt Mixtures - Ordoñez Huamán, Abel (2002)
In U.S. Asphalt mixtures have typically been designed with empirical laboratory design procedures. meaning that field experience is required to determine if the laboratory analysis correlates with pavement performance. However, even with proper adherence to these procedures and thedevelopment of mix design criteria, good performance could not be assured. The Superpave is a product of the Strategic Highway Research Program, SHRP. The SHRP was established by U.S. Congress in 1987, $150 million research program to improve the performance, durability of roadand the development of performance based asphalt specifications to directly relate laboratory analysis with field performance. The Superpave is being implemented by Americans agencies to replace the Marshall and Hveem design methods (actually used in Peru). The Superpave system optimises mixture resistance to permanent deformation, fatigue cracking and low temperaturecracking. In the early 1960's the European asphalt industry recognized a critical need for pavements which would be resistant to permanent deformation and the various pavement distresses associated with heavy traffic and low temperature. In response to this need, contractors developed Stone Mastic Asphalt, SMA a gap graded mix containing increased amounts of coarse aggregate, mineralfiller and asphalt cement as well as decreased amounts of fine aggregate and sand. This mixture proved so successful in Germany that its use was continued throughout Europe and actually in USA and Canada. The article presents the results of investigations in the National University ofEngineering for the application of the Superpave and SMA in Perú.